If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 18 = 5a + 6 Reorder the terms: 18 + 2a = 5a + 6 Reorder the terms: 18 + 2a = 6 + 5a Solving 18 + 2a = 6 + 5a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5a' to each side of the equation. 18 + 2a + -5a = 6 + 5a + -5a Combine like terms: 2a + -5a = -3a 18 + -3a = 6 + 5a + -5a Combine like terms: 5a + -5a = 0 18 + -3a = 6 + 0 18 + -3a = 6 Add '-18' to each side of the equation. 18 + -18 + -3a = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -3a = 6 + -18 -3a = 6 + -18 Combine like terms: 6 + -18 = -12 -3a = -12 Divide each side by '-3'. a = 4 Simplifying a = 4
| 7(7x-9)=67x+7v*8x | | 2x+2y+1+6y+x-6=180 | | 1/3x=-2/5 | | x+5x=336 | | 7/3+6x=2/3-7x | | 8x+16y+z=400 | | 4/e^3x | | 1.0047*8.2= | | 2(x+4)=3(2x-4) | | 2sin^2x=5cos^2x-3 | | Y=-.025x^2+x+6 | | x+2=2x+8 | | 4y+1=1 | | 4sin^2(2x)-2=0 | | 2ln(x+3)-3=0 | | 3x+2=-7+6x | | -4x-8x=-5-103 | | sec^2=2tan | | x+8x=-7+34 | | 5c+2=2c-7 | | 44=-6x+8 | | 5x-7x=3-5 | | -4x-2=23 | | -31=8x-(2x-5) | | 3(8x+16)-12=2+(7-3x) | | 4x^2-8x^2-96=0 | | 54(x^2+3)=0 | | (-7x/3)-1=-1-(7x/8) | | 35=x+(2x-1)+(2+14x) | | 4x-10+7(x-3)=0 | | 6(2+7x)+3x=9+6(9+8x) | | (2x+4y)+(2x-y)-(x-2y)= |